2004
DOI: 10.1111/j.1471-0307.2004.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different manufacturing parameters on the characteristics of Graviera Kritis cheese

Abstract: The objective of the present study was to improve the characteristics of Graviera Kritis cheese. The influence of lactic acid and propionic acid starters was studied and then the effect of washing and salting the curd combined with the use of starters was investigated. Although the traditional technology without starters resulted in the highest organoleptic characteristics, it was shown that the use of starters could improve texture characteristics of the cheeses if it is combined with a curd wash to control a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
1
12
1
1
Order By: Relevance
“…Moisture of the cheeses in the present study up to 90 d was similar to values reported by other studies on Graviera Kritis (Kandarakis et al, 1998;Nega & Moatsou, 2012). Moisture at 210 d was approximately 28%, which was lower than the 33e34% reported by Moatsou et al (2004). Apparently, the small size of cheese wheels in the present study facilitated dehydration.…”
Section: Gross Compositionsupporting
confidence: 81%
See 2 more Smart Citations
“…Moisture of the cheeses in the present study up to 90 d was similar to values reported by other studies on Graviera Kritis (Kandarakis et al, 1998;Nega & Moatsou, 2012). Moisture at 210 d was approximately 28%, which was lower than the 33e34% reported by Moatsou et al (2004). Apparently, the small size of cheese wheels in the present study facilitated dehydration.…”
Section: Gross Compositionsupporting
confidence: 81%
“…In general, at 90 d, the SN/TN ratios of the present study were lower than those reported for this cheese type by Moatsou, Kandarakis, Georgala, Alichanidis, and Anifantakis (1999). Average SN/TN values for marketed Graviera Kritis cheeses was 17.3 ± 3.8% (Nega & Moatsou, 2012) and values for this index approximately 20% or more have been reported for experimental cheeses (Moatsou et al, 1999(Moatsou et al, , 2004.…”
Section: Proteolysiscontrasting
confidence: 81%
See 1 more Smart Citation
“…The addition of Lb. helveticus to cheese increased the TCA‐SN values significantly as it enhanced the peptidase activity of the microorganisms (Moatsou et al. 2004).…”
mentioning
confidence: 99%
“…"Graviera Kritis" is a high quality hard cheese produced with the aid of both propionic and lactic acid bacteria fermentation, which has a slightly sweet taste and very pleasant organoleptic properties. It contains a moisture up to 35-38%, fat in dry matter at least 40-47% and no more than 2% salt (Moatsou et al 2004) Traditionally, it has been assumed that harmful microorganisms in cheese made with raw milk may be eliminated or reduced to safe levels during the cheese making process. Pathogenic microorganisms in raw milk die off during the cheese making, due to high acidity and competition with starter cultures (Fox 1993).…”
mentioning
confidence: 99%